Gender dynamics in scaling and commercialization of improved forages in Uganda - Lukuyu, Margaret; Sibiko, Kenneth W.; Notenbaert, An M. O. (2023)
Whereas planted forages are intended to enhance productivity and incomes in smallholder farms, improved livelihoods can be achieved and sustained only if they equally benefit women and men. This working paper is part of a larger study that assessed the gender dynamics in scaling and commercialization of improved forages in East Africa. Here we present results from Uganda based on data collected in December 2022 from gender-disaggregated Focus Group Discussions in Kiruhura and Ibanda Districts.